2016
DOI: 10.1016/j.algal.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modelling of Haematococcus pluvialis photoinduction for astaxanthin production in both attached and suspended photobioreactors

Abstract: Haematococcus pluvialis is a green algae with the great potential to generate natural astaxanthin. In the current study, dynamic models have been proposed to simulate effects of light intensity, light attenuation, temperature and nitrogen quota on cell growth and astaxanthin production in both suspended and attached photobioreactors, which to the best of our knowledge has not been addressed before. Based on the current models, optimal temperatures for algal growth and astaxanthin accumulation are identified. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Most importantly, there is a thriving international research interest, development and deployment of microalgae based sustainable and environmentally friendly technologies, by the health sector. This is with the aim of producing specialist high‐value products such as lutein (Xie, ), C‐phycocyanin (del Rio‐Chanona et al, ), and astaxanthin (Zhang, ), for which traditional synthesis routes and refinery methods from existing non‐renewable sources are expensive, energy intensive, and of low efficiency (Capelli et al, ; Yen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, there is a thriving international research interest, development and deployment of microalgae based sustainable and environmentally friendly technologies, by the health sector. This is with the aim of producing specialist high‐value products such as lutein (Xie, ), C‐phycocyanin (del Rio‐Chanona et al, ), and astaxanthin (Zhang, ), for which traditional synthesis routes and refinery methods from existing non‐renewable sources are expensive, energy intensive, and of low efficiency (Capelli et al, ; Yen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While nitrates are essential for biomass growth, high nitrate concentrations can severely supress the accumulation of biolipid (Mata et al, ). Consequently, the nitrate consumption rate was modeled using an adopted form of the the Monod model (Equation ), commonly used to simulate nutrient consumption (Pruvost, Degrenne, Titica, & Legrand, ; Zhang et al, ). dNdt=μNNN+KNX where N is culture nitrate concentration (mg L −1 ), KN is half‐velocity coefficient (mg L −1 ), and μN is maximum specific nitrate uptake rate (mg g −1 h −1 ).…”
Section: Materials and Modeling Methodologymentioning
confidence: 99%
“…Furthermore, photons in a PBR are either absorbed by microalgal biomass or scattered by bubbles, causing the local light intensity to diminish along the light transmission direction in the reactor. To take this light attenuation into account, a modified form of the Lambert‐Beer law has been proposed and has been widely utilized in recent studies, as shown in Equation (Zhang et al, ). μm(I)=μMI I+ks+I2ki I(z)=I0exp[(αX+β)z] where μM is maximum specific growth rate (h −1 ), I is light intensity (µmol m −2 s −1 ), ks and ki are light saturation term (µmol m −2 s −1 ) and light inhibition term (µmol m −2 s −1 ) for cell growth, respectively, I0 is incident light intensity (µmol m −2 s −1 ), α is cell absorption coefficient (m 2 g −1 ), β is bubble scattering coefficient (m −1 ), z is the distance from light source (m), and L is the width of the PBR (m).…”
Section: Materials and Modeling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Researches on H.pluvialis have taken place over several decades, mostly focused on cell differentiation [4], astaxanthin metabolism[5], cultivation methods [6] and astaxanthin extraction technology[7]. Continuous efforts were made to improve its cellular growth and the level of astaxanthin accumulation through traditional mutagenesis of H.pluvialis [8]; however there are no reports of phenotypic modification through genetic engineering methods.…”
Section: Introductionmentioning
confidence: 99%